ESL Learning method preference of form four students in SMK Sungai Tong / Mohd Fakhzani Sulong - Sulong, Mohd Fakhzani (2011)
The purpose of the study is to identify ESL learning method preference of form four students in SMK Sungai Tong. There are two types of teaching methods that are currently used, namely student-centered and the teacher-centered. The respondents were all form four students in SMK Sungai Tong in 2011. This survey was conducted by using questionnaires. The questionnaires consist of four different sections which are Section A: Demographic Profiles, Section B: Students’ Exposure to English, Section C: Teaching method preference, and Section D: Students’ interest in learning English. For sections B, C and D all answers were recorded by using five points Likert scale. The result of the study showed that majority of the student preferred student-centered learning. Information such as demographic background, exposure to English and motivation level were discussed as the main factors for the findings.